Burden of esophageal cancer and its attributable risk factors in 204 countries and territories from 1990 to 2019 - Yanqing Cai; Jianxiong Lin; Wenbo Wei; Peixing Chen; Kaitao Yao (Frontiers Media S.A., 2022)
BackgroundEsophageal cancer is a global health concern. Regularly updated data about the burden of esophageal cancer are essential for formulating specific public policies. We aimed to estimate the global, regional, and national burden and trends of esophageal cancer and its attributable risk factors from 1990 to 2019, by age, sex and socio-demographic index (SDI).MethodsData about the incidence, death, disability-adjusted life-years (DALYs), and age-standardized rates were collected from Global Burden of Disease study 2019. Estimated annual percentage changes were used to quantify the temporal trends of age-standardized rates. Moreover, the risk factors attributable to esophageal cancer deaths were also presented.ResultsThere were 534,563 incident cases and 498,067 deaths in 2019, contributing to 11,666,017 DALYs. The absolute numbers of incidence, death, and DALYs had increased from 1990 to 2019, contrasting with declined changes in their corresponding age-standardized rates. The burden of esophageal cancer varied across different regions and countries, and the age-standardized rates were negative with SDI. Almost half of the esophageal cancer was concentrated in China. Males accounted for most of the burden of esophageal cancer, and the onset age tended to be older. The death of esophageal cancer was primarily attributable to smoking, followed by alcohol use, high body mass index, diet low in fruits and diet low in vegetables.ConclusionThe burden of esophageal cancer was heterogeneous across regions and countries by sex, age, and SDI, providing information for governments that may help to formulate more targeted policies.